Comparing the cobas Influenza A/B Nucleic acid test for use on the cobas Liat System (Liat) with rapid antigen tests for clinical management of Japanese patients at the point of care. - Hiroshige Mikamo; Yusuke Koizumi; Yuka Yamagishi; Nobuhiro Asai; Yuko Miyazono; Toshikazu Shinbo; Michiko Horie; Kenichi Togashi; Elissa M Robbins; Nobuo Hirotsu (PLoS ONE, 2022)
Background Rapid diagnosis of influenza is critical in preventing the spread of infection and ensuring patients quickly receive antiviral medication to reduce the severity and duration of influenza symptoms, whilst controlling the spread of the causative virus. In Japan patients are often administered anti-influenza medication following a positive rapid antigen detection test (RADT) result. However, the sensitivity of RADTs can lead to false negative results. The cobas® Influenza A/B Nucleic acid test for use on the cobas Liat® System (Liat) is a molecular point-of-care method that can provide a more sensitive alternative to RADTs for rapid influenza diagnosis and treatment. Methods In this prospective multicenter study, diagnostic performance of the Liat test was compared with RADTs in patients presenting with influenza-like-illness. Test performance was also assessed by time since symptom onset. Results Of 419 patients enrolled, 413 were evaluable for all designated tests. Most patients had type-A infection, and only one patient had influenza type B. In 413 patients, the sensitivity and specificity (95% CI) of the Liat test were 99.5% (97.2-99.9%) and 99.5% (97.4-99.9%), respectively, and were 79.7% (73.5-84.7%) and 95.4% (91.7-97.5%) for RADTs. For patients tested <12 hours from symptom onset, the Liat test had significantly higher sensitivity than RADTs (p<0.0001). Conclusion Overall, compared with standard of care RADTs, the Liat test was more sensitive and specific in children and adults, particularly in the early stages of infection. Greater sensitivity can enable earlier diagnosis and may better inform appropriate antiviral treatment decisions.